Antineoplastic effect of compounds C14 and P8 on TNBC and radioresistant TNBC cells by stabilizing the K-Ras4BG13D/PDE6δ complex - Carrión-Estrada, Dayan A.; Aguilar-Rojas, Arturo; Huerta-Yepez, Sara; Montecillo-Aguado, Mayra; Bello, Martiniano; Rojo-Domínguez, Arturo; Arechaga-Ocampo, Elena; Briseño-Díaz, Paola; Meraz-Ríos, Marco Antonio; Thompson-Bonilla, María del Rocío; Hernández-Rivas, Rosaura; Vargas, Miguel (Frontiers in Oncology, 2024)
Breast cancer (BC) stands as the leading cause of cancer-related deaths among women, with triplenegative breast cancer (TNBC) representing one of the most aggressive and treatment-resistant subtypes. In this study, we evaluated the antitumoral potential of C14 and P8 molecules in both TNBC and TNBC-radioresistant cells. These compounds have the capability to stabilize the complex formed by the overactivated form of K-Ras4B G13D and its membranal transporter (PDE6δ). Western blot analysis revealed that C14 and P8 had a negative impact on the activation of K-Ras signaling pathways in MDA-MB-231 and MDA-MB-231RR. Moreover, proliferation assays demonstrated their efficacy as cytotoxic agents, with a preference for inducing apoptosis as the primary mode of cell death. Importantly, these compounds exhibited the capacity to inhibit the clonogenic capability of TNBC cells and P8 in TNBC-radioresistant cells. Furthermore, in an in vivo model, C14 and P8 inhibited tumor growth and reduced markers of proliferation, angiogenesis, and cell cycle progression. In conclusion is suggested that, both drugs could be used as adjuvant treatment for TNBC patients or those who have not responded to standard radiotherapy or other traditional treatments.